Explore Alternative Ways in Measuring Competitiveness in Insurance Markets in UK - Thoppil Sivasankaran, Prasanth (2006)
This research explores competency in the UK general insurance market by using different measures of competency. The study uses different product lines from the UK general insurance markets from 2000 to 2004. The basic methodologies used in this study are Herfindhal index, 5 and 8 firm's concentration ratio.